THU0229 AMPHIREGULIN ATTENUATES LUPUS NEPHRITIS VIA SUPPRESSION OF PRO-INFLAMMATORY T-CELL FUNCTIONS IN AN ANIMAL MODEL OF SLE. (June 2019) - Melderis, Simon; Warkotsch, Matthias; Hagenstein, Julia; Herrnstadt, Georg; Tiegs, Gisa; Steinmetz, Oliver
Abstract : Background: Amphiregulin (AREG) is a member of the epidermal growth factor (EGF) family and plays a role in development, tissue homeostasis and tumorigenesis. Recently, however, AREG has also emerged as novel player in immunity. Interestingly, AREG expression was shown to be one of the most highly upregulated transcripts in peripheral blood leukocytes of patient with systemic lupus erythematosus (SLE) [1]. The functional role of AREG in SLE, and inflammation in general, remains unclear to date and both, pro- and anti-inflammatory functions have been postulated [2, 3]. Objectives: Our aim was to investigate the role of AREG in the mouse model of pristane induced lupus (PIL) with particular focus on lupus nephritis (LN). We further wanted to identify target cells and mechanisms by which AREG exerts its immunomodulatory effects. Methods: PIL was induced in AREG knock-out (KO) mice and wild type controls. Animals were sacrificed at pre-specified time points. Renal histology, immune complex deposition, leukocyte influx and mRNA expression levels were analyzed. Furthermore, broad in vivo and in vitro analyses of renal and systemic immune responses were carried out. Results: Renal AREG mRNA expression significantly increased during development of LN, indicating functional relevance. Indeed, lupus nephritis was significantly aggravated in AREG-KO mice both at early (9 months) and later (12 months) stages after PIL induction. In line with this, we noted an increased deposition of immune complexes and renal influx of pro-inflammatory leukocytes (CD3 + T-cells, macrophages and neutrophils). In addition, we found the CD4 + T-cells of AREG-KO mice to have a more pro-inflammatory phenotype with significantly increased production of pro-inflammatory cytokines (IFNγ and IL-17A) both in ex-vivo culture, as well as FACS-analyses of nephritic kidneys. Mechanistically, we found that AREG treatment of spleen cell cultures potently suppressed cytokine production. More detailed evaluation by further in-vitro studies indicated, that AREG can directly suppress cytokine production by effector CD4 + T-cells as well as enhance the suppressive capacity of FoxP3 + regulatory T-cells (Tregs). Conclusion: These data show that AREG has a protective role on development of LN induced by pristane, which might be therapeutically exploited. Our results further suggest, that direct effects on CD4 + T-effector cells, as well as indirect effects via Tregs, are two mechanisms by which AREG exerts its protective role. References: [1] Ishii, T., et al., Isolation and expression profiling of genes upregulated in the peripheral blood cells of systemic lupus erythematosus patients. DNA Res, 2005. 12(6): p.429-39. [2] Kefaloyianni, E., et al., ADAM17 substrate release in proximal tubule drives kidney fibrosis. JCI Insight, 2016. 1(13). [3] Zaiss, D.M., et al., Amphiregulin enhances regulatory T cell-suppressive function via the epidermal growth factor receptor. Immunity, 2013. 38(2): p.275-84. Disclosure of Interests: None declared